IMPULSE BUYING KONSUMEN SHOPEE: PERAN SALES PROMOTION, HEDONIC SHOPPING MOTIVATION, DAN SHOPPING LIFESTYLE - Radito, Thomas Aquinas; Chrisanty Fan Au, Sonia; Srining Prapti, Meniek (Jurnal Socia Akademika, 2025)
The increase in the value of e-commerce transactions in Indonesia is accelerating, rising from IDR 205.5 trillion in 2019 to IDR 487.01 trillion in 2024. This phenomenon reflects the increasing public interest in online shopping, people tend to make purchases online more often than they shop directly on the spot. Shopee as one of the e-commerce in Indonesia based on data from Semrus is in the top 10 websites with the most visitors in Indonesia in 2024. The ease of access to e-commerce that provides information on goods, shopping facilities, and online payments has encouraged the emergence of the impulse buying phenomenon. This study examines the influence of sales promotion, hedonic shopping motivation, and shopping lifestyle on impulse buying. The research was conducted in Yogyakarta with a sample of 200 respondents. The sample method uses purposive sampling with the criterion that respondents must have an application and a Shopee account and make at least 1x purchases within the past month. Data was obtained using a questionnaire distributed using google form. Validity test using Pearson Product Moment and reliability test using Cronbach Alpha. Data analysis uses multiple regression. The results of the study showed that only hedonic shopping motivation and shopping lifestyle had a significant effect on impulse buying, while sales promotion did not have a significant effect on impulse buying.